A Covalent Triazine Framework, Functionalized with Ir/N-Heterocyclic Carbene Sites, for the Efficient Hydrogenation of CO2 to Formate - Gunasekar, Gunniya Hariyanandam; Park, Kwangho; Ganesan, Vinothkumar; Lee, Kwangyeol; Kim, Nak-Kyoon; Jung, Kwang-Deog; Yoon, Sungho (AMER CHEMICAL SOC, 2017)
Functionalizing the recently developed porous materials such as porous organic frameworks and coordination polymer networks with active homogeneous catalytic sites would offer new opportunities in the field of heterogeneous catalysis. In this regard, a novel covalent triazine framework functionalized with an Ir(III)-N-heterocyclic carbene complex was synthesized and characterized to have a coordination environment similar to that of its structurally related molecular Ir complex. Because of the strong sigma-donating and poor pi-accepting characters of the N-heterocyclic carbene (NHC) ligand, the heterogenized Ir-NHC complex efficiently catalyzes the hydrogenation of CO2 to formate with a turnover frequency of up to 16 000 h(-1) and a turnover number of up to 24 300; these are the highest values reported to date in heterogeneous catalysis for the hydrogenation of CO2 to formate.
Keywords: CARBON-DIOXIDE HYDROGENATION; FORMIC-ACID; CATALYTIC-HYDROGENATION; IRIDIUM CATALYST; WATER OXIDATION; COMPLEXES; RUTHENIUM; POLYMERIZATION; EQUILIBRIUM; CONVERSION